Video game disorder, gaming patterns, and impulsivity in a sample of Portuguese young adults - Leite, Nuno (2024)
International studies on the relationship between videogame disorder and impulsivity focus on a neurocognitive perspective, highlighting decreased brain activity in regions related to inhibitory control caused by video game disorder, leading to difficulties in decision-making and impulse inhibition. The relevance of this study is primarily based on the lack of international research on this relationship, the very small number of studies in the Portuguese context addressing gaming disorder, and the absence of studies in Portugal that relate these two variables. Aim: to explore the relationship between video game disorder, gaming patterns, and impulsivity in a sample of Portuguese young adults. Method: 163 subjects, aged between 18 and 25 years, who play video games, fulfilled a sociodemographic questionnaire on gaming patterns, the Short Internet Gaming Disorder Scale, and the Barratt Impulsiveness Scale. Results: Only 1.2% had a high risk of excessive and harmful gaming. Videogame disorder is positively correlated with impulsivity, which is more common in males, and that earlier that someone starts to game the higher the possibility of higher levels of video game disorder. Younger adults have higher levels of videogame disorder, and the preferred gaming platform is the computer, which is also associated with higher levels of gaming disorder. The amount of money spent on in-game purchases contributes to video game disorder and is influenced by impulsivity. Discussion: This study lays the groundwork for future research and highlights the need for prevention actions among younger populations.